2011
DOI: 10.1007/s00374-011-0646-1
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity of rhizobia associated with alfalfa in Serbian soils

Abstract: We have evaluated the genetic diversity and phylogeny of alfalfa rhizobia, originating from different types of soils in Serbia and their ability to establish an effective symbiosis with alfalfa (Medicago sativa L.). A collection of 65 strains isolated from root nodules of alfalfa were characterized by rep-PCR analysis, partial and complete 16S rDNA gene and recA gene sequencing, as well as atpD gene sequencing and DNA-DNA hybridizations. The results of the sequence analyses revealed that Sinorhizobium meliloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Comparing the detected concentrations of IAA in Bradyrhizobium and Ensifer strains indicates a clearly lower production in representatives of the genus Bradyrhizobium. These results are in agreement with the findings of Stajković-Srbinović et al, (2012;2020), which showed a weaker production of auxin by Bradyrhizobium spp. strains compared to Sinorhizobium spp.. B. japonicum strains are known to synthesize IAA, both as free-living forms in soil and as bacteroids in soybean nodules (Hunter, 1987;Minamisawa and Fukai, 1991).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Comparing the detected concentrations of IAA in Bradyrhizobium and Ensifer strains indicates a clearly lower production in representatives of the genus Bradyrhizobium. These results are in agreement with the findings of Stajković-Srbinović et al, (2012;2020), which showed a weaker production of auxin by Bradyrhizobium spp. strains compared to Sinorhizobium spp.. B. japonicum strains are known to synthesize IAA, both as free-living forms in soil and as bacteroids in soybean nodules (Hunter, 1987;Minamisawa and Fukai, 1991).…”
Section: Resultssupporting
confidence: 93%
“…Most of the strains belonging to Ensifer meliloti species (Stajković-Srbinović et al, 2012) reached the highest detectable level of IAA of 200 µg ml -1 (designated as ≥200 µg ml -1 ), while the lowest detected concentration was 15 µg ml -1 . The strains producing 15 µg ml -1 of IAA belong to Rhizobium tibeticum species, whereby visual observation IAA production could not be detected (color change).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to that, it had been an alfalfa field for 4 years. Like cowpea, alfalfa is a legume; however, it generally associates with Ensifer, and does not form nodules with Bradyrhizobium (Stajković-Srbinović et al 2012;Wang et al 2018;Woliy et al 2019). Bioinoculants such as the one used at Shafter are employed to prime soils without a history of successful prior production of a particular legume, making this site a perfect candidate for inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ramírez-Bahena and others (34) showed that under controlled conditions, inoculation of alfalfa with selected acid-tolerant strain improved plant biomass production. In Serbia, where the use of commercial inoculants for alfalfa is not a common practice (52) , Stajkoviae-Srbinoviae and others (47) found that in soils with pH between 5.1 and 8.1 most of the nodules of M. sativa were occupied by E. meliloti. Additionally, Deliae and others (52) identified effective native alfalfa strains in acid soils, which represented an interesting finding because 50% of Serbia's arable soils are acid.…”
Section: Response Of Alfalfa To Inoculationmentioning
confidence: 99%